(3GdLhGgQ GdKejfI aj ePgH YGde GdeOjfIs - (3CHh eMeO YHO Gddg Hf eMeO Hf fLe Hf TGS GdeUQj (B( (3Hf fRGQ GdLPGej(B)(3,J (B610 (3g` s ((3YKeGf Hf GdMGL eMeO Hf YHO Gddg Hf EHQGgje GdbQTi GdYHOQi s)
(3ChdgG (B:s
(3Chd GdehLhO efg CKfGA HGH GdYGQjI (B:( (3hGdeSJYjQ ef GdZGUH jVef EPG JdaJ GdYGQjg JMJ jOg (B) s
(3BNQgG (B:s
(3ced GdcJGH GdeSei (B( (3HYbO (B) (3GdLhGgQ GdKejfI HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdI ELGRI HeOjfI CTHjdjI SfI (B621 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs